Pemanfaatan ARCore Geospatial untuk Simulasi Banjir sebagai Media Edukasi Kebencanaan - I Gede Dhananjaya; Kadek Yota Ernanda Aryanto; I Gede Partha Sindu (YASIN, 2026)
Although Augmented Reality (AR) technology has been widely applied in various educational contexts, studies that specifically integrate ARCore Geospatial technology for location-based flood simulation as a disaster education medium remain limited. This study aims to develop and evaluate an ARCore Geospatial-based flood simulation application as a disaster education medium. This study used a Research and Development (R&D) approach with the Multimedia Development Life Cycle (MDLC) model, involving 30 students selected using a convenience sampling technique. Data were collected through black-box testing, expert validation instruments, and the User Experience Questionnaire (UEQ), then analyzed using functional testing results, Gregory validity analysis, and descriptive UEQ analysis. The results show that all application features function according to the development objectives. The expert validation results show that the media and application design aspects received very high ratings, although several suggestions were provided to improve the content aspect. In addition, the UEQ results show a positive user experience across all evaluated dimensions, namely attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. These findings contribute to the development of disaster education media by demonstrating the potential of geospatial-based Augmented Reality in supporting contextual and interactive learning experiences. The conclusion of the study affirms that location-based flood simulation through ARCore Geospatial can support disaster education and increase flood mitigation awareness through contextual and interactive visualization. The implications of this study provide practical contributions for educational institutions and disaster stakeholders in developing educational strategies that are more engaging, innovative, and location-based. Future research is recommended to integrate real-time environmental data and expand the application implementation to broader geographical areas.